In silico study of SARS‐CoV‐2 spike protein RBD and human ACE‐2 affinity dynamics across variants and Omicron subvariants. Issue 1 (27th December 2022) - Abeywardhana, Shamali; Premathilaka, Malinda; Bandaranayake, Upeka; Perera, Deshan; Peiris, L. Dinithi C.
Abstract: The coronavirus disease 2019 virus outbreak continues worldwide, with many variants emerging, some of which are considered variants of concern (VOCs). The WHO designated Omicron as a VOC and assigned it under variant B.1.1.529. Here, we used computational studies to examine the VOCs, including Omicron subvariants,  and one variant of interest.  Here we found that the binding affinity of human receptor angiotensin‐converting enzyme 2 (hACE2) and receptor‐binding domain (RBDs) increased in the order of wild type (Wuhan‐strain) < Beta < Alpha < OmicronBA.5 < Gamma < Delta < Omicron BA.2.75 < BA.1 < BA.3 < BA.2. Interactions between docked complexes revealed that the RBD residue positions like 452, 478, 493, 498, 501, and 505 are crucial in creating strong interactions with hACE2. Omicron BA.2 shows the highest binding capacity to the hACE2 receptor among all the mutant complexes. The BA.5's L452R, F486V, and T478K mutation significantly impact the interaction network in the BA.5 RBD‐hACE2 interface. Here for the first time, we report the His505, an active residue on the RBD forming a salt bridge in the BA.2, leading to increased mutation stability. When the active RBD residues are mutated, binding affinity and intermolecular interactions increase across all mutant complexes. By examining the differences in different variants, this study may provide a solid foundation for structure‐based drug design for newly emerging variants.